Analisis Akuntabilitas Distribusi dan Bantuan Sosial - Sudarwadi, Hustianto; Yarangga, Hilda Christine; Werimon, Simson Christine (Lensa Ekonomi, 2024)
The aim of this research is to determine the mechanism for planning, implementing and administering monitoring and evaluating the distribution of Social Assistance Funds in Manokwari Regency. Second, to determine the factors inhibiting the planning, implementation and administration, monitoring and evaluation of the distribution of Social Assistance Funds in Manokwari Regency. The sampling technique used was purposive sampling. The research results show that the Beneficiary Families (KPM) of the Social Assistance Program in Manokwari Regency in West Manokwari District with a satisfaction level percentage of 85.71% seen from the assessment of service, distribution, amount received and period of receipt, while 1 (one) KPM with a percentage of 14.29% dissatisfied with the service, distribution, amount received and time period received. The Social Assistance Organizer is seen from 4 (four) aspects of Accountability namely: planning, distribution, accountability and Monitoring Evaluation with the percentage level of conformity to the Accountability aspect is 100% for the Social Service, while for the East Manokwari District Office the percentage level of conformity is 50% seen from 2 (two) aspects of accountability, namely: planning and distribution have not been implemented optimally and well. Data verification has not been carried out optimally by District Social Welfare Workers so that the distribution process is not on target.